The savings and growth nexus in Bangladesh - Rahman, Dr. Sultan Hafeez; Hafeez, Dr. Sultan (BIGD, 2024)
The paper investigates the causal relationship between Bangladesh’s gross domestic savings (GDS) and gross domestic product (GDP) in the years 1980 to 2018. Using yearly time series data from the period, the authors employ one long-run and two short-run causality tests to identify the direction of causality between the two variables. Bangladesh experienced stellar GDP growth between 1990 and 2019, averaging 6.5 percent per year. In the latter years, this rate was over 7 percent per year. Despite that, its GDS rate only increased to 22 percent from 15 percent in the same period. This is in stark contrast to the scenario in countries like India, China, Indonesia, and Thailand. The Philippines, however, had a low savings rate like Bangladesh. A common feature of both countries is their large remittances and the broad-based growth effects in the economies. In both Bangladesh and the Philippines, gross national savings (GNS) rather than GDS caused greater investment. Thus, domestic savings were clearly not the key driver of growth in Bangladesh, which is inconsistent with the view of capital fundamentalists and neoclassical growth theory. The findings suggest that, in the short run, the direction of causality between savings and economic growth is unidirectional from economic growth to savings. And in the long run, there is no evidence of statistically significant causality in either direction. In other words, higher economic growth induced savings in Bangladesh in the studied period of time.